Design of a Community Ownership and Preparedness Index: using data to inform the capacity development of community-based groups. (24th July 2012) - Thomas, Tom; Narayanan, Pradeep; Wheeler, Tisha; Kiran, Usha; Joseph, M J; Ramanathan, T V
Abstract : Background: Community mobilisation is an important component of a participatory approach to health and development interventions. However, it is challenging to define, measure and assess community participation and ownership of a programme, especially at scale. Methods: An iterative cross-sectional survey was designed for implementation across a representative sample of community-based groups, using a weighted index that captured both qualitative and quantitative data in a standardised form. These data were aggregated at the level of individual groups, as well as state-wide or across the whole programme. Community participation in the survey is a primary feature of the methodology and was integral to the process of designing the index and administering the survey. Results: The survey provided programme management and communities with objective tools for monitoring community mobilisation across a large-scale and complex intervention covering 32 districts in India. The implementation of the survey engaged communities in an open discussion of their goals and capabilities and helped them to challenge the power dynamics between themselves and other stakeholders. Conclusions: It is possible to translate the theoretical premises of participatory development into a tool that both measures and fosters meaningful participation. The active participation of community members in the collection and analysis of data on their mobilisation suggests that monitoring of participation can be undertaken to inform a scaled-up programme and can be a useful intervention in its own right.